2018
DOI: 10.1007/s00277-018-3302-0
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune disorders are common in myelodysplastic syndrome patients and confer an adverse impact on outcomes

Abstract: The coexistence of autoimmune disorders (AD) in patients with myelodysplastic syndrome (MDS) or chronic myelomonocytic leukemia (CMML) has been widely recognized, although with distinct results regarding their prevalence and impact on the outcomes of the underlying hematological process. This study was aimed to analyze the prevalence, clinical characteristics, and outcomes of MDS with AD in a series of 142 patients diagnosed with MDS and CMML. AD was ascertained by both the presence of clinical symptoms or com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 31 publications
0
33
0
1
Order By: Relevance
“…2,3 In addition, concomitant autoimmune diseases are common in MDS; in a recent study, 48% of patients with MDS had serological or clinical evidence of an autoimmune disease, which was found to be an independent marker for a worse prognosis. 4 IST with antithymocyte globulin (ATG), [5][6][7][8] cyclosporine, [9][10][11] or alemtuzumab, 12 as well as IST combinations of ATG with cyclosporine [13][14][15][16][17] or etanercept, 18 have all been studied in this context. Although some studies reported clinical activity with IST, others were not able to confirm a benefit of IST in unselected or older patients with MDS.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 In addition, concomitant autoimmune diseases are common in MDS; in a recent study, 48% of patients with MDS had serological or clinical evidence of an autoimmune disease, which was found to be an independent marker for a worse prognosis. 4 IST with antithymocyte globulin (ATG), [5][6][7][8] cyclosporine, [9][10][11] or alemtuzumab, 12 as well as IST combinations of ATG with cyclosporine [13][14][15][16][17] or etanercept, 18 have all been studied in this context. Although some studies reported clinical activity with IST, others were not able to confirm a benefit of IST in unselected or older patients with MDS.…”
Section: Introductionmentioning
confidence: 99%
“…Fluctuations in platelet count may have suggested accompanied autoimmune mechanism, immune thrombocytopenia. 7 …”
Section: Case Reportmentioning
confidence: 99%
“…Autoimmune hemolytic anemia has been reported in association with MDS [57][58][59]. Association of systemic lupus erythematosus and MDS has been reported [60][61][62].…”
Section: Miscellaneousmentioning
confidence: 99%